Research progress on the role of the NEIL family in cancer - Chen, Yinghan; Ma, Muyun; Zou, Aixue; Wang, Xinjia; Dong, Weiwei (Frontiers in Cell and Developmental Biology, 2025)
Cancer is the primary cause of death worldwide. Cancer occurrence and progression are closely associated with DNA damage repair. DNA glycosylase were the first enzymes to initiate base excision repair, and the Nei-like DNA glycosylase (NEIL) family has attracted increasing attention as an important component of DNA glycosylases. Here, we introduce the role of the NEIL family in the malignant biological behaviors of cancer, including cell proliferation, chemoradiotherapy resistance, invasion and migration, apoptosis, and stemness. Mechanisms affecting the expression of the NEIL protein family range from the transcriptional level and mRNA editing to the level of post-translational modification. Additionally, we emphasize the different functions of the NEIL family in various malignancies and present useful information that supports the hypothesis that the NEIL family could be a potential target in the treatment and diagnosis of various cancers.